UNFORESEEN EFFECTS ON PNAIC IMPLEMENTATION: UNFORESEEN EFFECTS ON PNAIC IMPLEMENTATION - Ramos, Maria Elizabete Neves (2020)
This study aims to analyze underseen effects of the National Pact of Literacy at the Right Age (PNAIC) which had as its main axis the continuing education of literacy teachers. PNAIC was a nationwide policy based on the collaborative regime involving the three federated entities. The policy, although formulated by the federal government, was materialized in the municipalities, which eventually had an unanticipated effect on policy formulation: PNAIC literacy teachers, because of their incentives, went in search of more training than just education offered by PNAIC at both undergraduate and postgraduate levels. This has generated symbolic and material effects for municipal management, which will need to deal with these effects locally. This study, based on a broader research, used documentary analysis, interviews with political actors and a statistical survey of data from different years of the School Census on the change in the educational level of literacy teachers in municipal schools from the state of Rio de Janeiro.